2021
DOI: 10.1111/clr.13699
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized clinical trial evaluating the effects of two different implant collar designs on peri‐implant healing and functional osseointegration after 25 years

Abstract: Objectives Evaluate the effects of two different machined‐collar lengths and designs on peri‐implant healing. Material and Methods An implant with a microtextured surface and 3.6mm‐long internal‐connection machined collar was compared to two implants that had an identical 1.2mm‐long external‐connection machined collar, but one had the microtextured surface while the other's was machined. Participants received the three implants, with microgap at the crest, alternately at five sites between mental foramen, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…used implants with a diameter of 3.75 mm and compared implants with smooth collar to the microtextured collar. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…used implants with a diameter of 3.75 mm and compared implants with smooth collar to the microtextured collar. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…and Camarda et al , the use of a machined collar showed better results in maintaining marginal bone height than microthreaded or microtextured implant collar. [ 21 , 28 ] Apart from the results of measuring the marginal bone height, Camarda et al . found that the PD and bleeding index in the machined collar group had slightly better results than the microtextured collar group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to evaluate the efficacy of the applied surface conditioning liquid for the repair of chipping fractures. Ceramic chipping is the most prevalent technical complication (followed by framework fractures) among fixed dental restorations 1–3,18 . In single‐implant crowns, the 5‐year incidence data reported in the literature shows veneering ceramic chipping rates of 2.9% for metal‐ceramic and 2.8% for zirconia‐ceramic restorations 9 .…”
Section: Discussionmentioning
confidence: 99%
“…cal success for partially and fully edentulous patients over the last three decades. 1,2 Dental ceramics are widely used in these types of restorations for veneers on metal or ceramic frameworks, and even in monolithic restorations, due to their good esthetics, natural appearance, and favorable optical properties. [3][4][5] Although designs and manufacturing techniques have evolved remarkably, chipping of the veneering ceramic or framework fracture, still occur independent of the material.…”
mentioning
confidence: 99%